metaphor Imagery in Mohammed Belkacem Khammar poetry -Artistic study- (مجلة إحالات, 2026)
The metaphor image is a rhetorical art and one of the methods that have a special creative ability, as it is the best way to display the ideas and feelings that exist in the poet’s imagination. It gives a clear aesthetic aspect to the texts that are employed in it. Moreover, itwas considered a fundamental pillar in the formation of the poetic fabric, as it is an importantpillar in the construction of the text, and in light of the above, this research came with its descriptive and analytical method to reveal to us the technical and semantic dimensions of thegraphic images in the poetry of Muhammad Belkacem Khamar, and the extent of its effect onthe recipient Focusing on his intellectual and emotional aesthetics, the study also focused onshowing those graphic patterns, how to employ them, and their effectiveness in coloring thecapillary tissue.